Jurassic Park - Kennedy, Kathleen; Molen, Gerald; Spielberg, Steven (USA : Universal Studios [production company] ; Kuala Lumpur : Berjaya HVN Sdn. Bhd. [distributor], 1992)
A masterpiece of imagination, suspense, science and cinematic magic that has quickly become the most successful film in worldwide box-office history
Editor, Michael Kahn ; screenplay, Michael Crichton, David Koepp
Cast : Sam Neil, Laura Dern, Jeff Goldblum, Richard Attenborough
Keywords: Dinosaurs in motion pictures